The Kenya Portable Battery Pack Experience : Text Marketing an Alternative for Low-Income Rural Household Electrification - World Bank (Washington, DC, 2014)
The Kenya Portable Battery Pack Project is the most recent of several ESMAP activities building the Kenya solar photovoltaic (PV) commercial infrastructure through market study and small interventions. The five ESMAP studies have done the following: determined which PV system components rural people desire and how they purchased them; developed pilot financing mechanisms with companies and credit groups; helped develop low-cost product concepts; and increased the capacity of both urban and rural market players to serve the market. The overall purpose fo the Battery Pack and Jua Tosha activities was to examine the viability of lowest-cost options for delivering electricity services to the rural poor. Given the well-developed nature of the Kenya PV market and the tendency of consumers to purchase very small systems in an incremental fashion, this project attempted to introduce a product that met end-users needs in terms of both low incremental purchase cost and greatly improved features over old systems.